Only Mexicans there: The nation as inequality regime and methodological nationalism in migration studies. (15th January 2018) - Hayden, Bridget A
Abstract: This article draws on de-colonial studies to explore an alternative to methodological nationalism. Methodological nationalism has been justly criticized in migration studies for the assumptions it smuggles into social theory. However it is difficult to avoid not only because it is so deeply engrained in the epistemology of the West but also because migration is the consequence of the on-going political importance of nation-states. This paper explores an alternative approach that takes the nation as integral to the study of migration. Drawing on de-colonial studies I suggest analyzing national identity as an inequality regime entangled with other inequality regimes.